Influence of Pongamia pinnata Leaf Extract based Silver Nanoparticles Towards the Degradation of Safranin O Dye - Alvin Kalicharan, A.; Anbarasan, V.; Priyanka, R.; Arivalagan, K. (Asian Journal of Chemistry, 2023)
Use of medicinal herbs for green synthesis of nanoparticles has attracted researchers owing to their valuable influence on mankind. Benefit of consuming plants aimed at greener production of nanomaterials relies on the less toxicity and cost-effective protocol. Herein, we reported the synthesis of biocompactible silver nanoparticles using Pongamia pinnata leaf extract. The biomolecules existing in leaf extract of Pongamia pinnata played dual role for capping and equilibrium of silver nanoparticles. Phenomena of surface plasmon resonance was observed from the UV-Vis spectrum around 426 nm. The FTIR peaks revealed the significance of biomolecules in the formation of stable silver nanoparticles. From XRD pattern, peaks attained has better covenant with Ag in metal form with face-centered-cubic feature. Morphology of silver nanoparticles from SEM and TEM studies revealed that the particles are spherical in shape. Degradation of safranin O dye using green synthesized silver nanoparticles exhibited better degradation efficiency. Without much advent process, this method for synthesizing silver nanoparticles provides an inexpensive and environmentally responsible approach.